A Study on The MSMEs Growth of Es Teh Nurul Jumbo and Potato Curly Crunch at Polbeng Business Expo Chapter II - Melda Irwan Pratama; M. Alkadri Perdana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Polbeng Business Expo Chapter II is an event organized by sixth-semester students from the International Business Administration Study Program under the auspices of the Commercial Administration Department as part of their final project. This event focuses on the growth of micro, small, and medium enterprises (MSMEs) and offers various entertainment activities, including fashion shows, music performances, and other art events. This study aims to analyze the implementation of Polbeng Business Expo Chapter II, including the application of digital promotion, the use of QRIS as a cashless payment system, and the preparation of financial reports to support MSME development. Data was obtained from exhibition visitors to assess the extent to which this event had an impact and was effective in developing MSMEs. The findings show that the exhibition succeeded in attracting public attention, provided a useful and informative experience for visitors, and was well executed. In addition, the implementation of digital promotion and the use of QRIS were considered to have increased the convenience of transactions and expanded the marketing reach for MSMEs. The preparation of financial reports was also proven to be important in increasing transparency and accountability in MSME financial management. Thus, the implementation of Polbeng Business Expo Chapter II, supported by digital promotion, the QRIS payment system, and regular financial reports, can have a positive impact on the development of MSMEs.